The impact of biochemical marker levels in pregnant patients diagnosed with HELLP syndrome on predicting the progression and recovery timelines - Sapmaz, Mehmet Alican; Erbey, Sait; Polat, Murat; Kurt, Ahmet; Kurt, Dilara Sarıkaya; Yakut Yücel, Kadriye; Ağaoğlu, Recep Taha (The European Research Journal, 2025)
Objectives: This study investigates the role of biochemical markers in predicting the clinical course of pregnant women with Hemolysis, Elevated Liver Enzymes and Low Platelets (HELLP) syndrome, aiming to correlate marker levels with disease progression and recovery timelines for improved prognostic assessment and therapeutic strategies. Methods: A retrospective analysis was conducted on 50 pregnant patients (aged 18-45) diagnosed with HELLP syndrome between October 2022 and November 2023. Data on demographics, vital signs, clinical symptoms, and laboratory markers (platelets, liver enzymes, lactate dehydrogenase [LDH], and bilirubin) were examined. Outcomes measured included complications, intensive care unit needs, and recovery time. Results: The mean age was 30.74±5.27 years and body mass index of 29.76±5.88 kg/m2. The gestational age was 31.97±4.45 weeks. Significant cut-off values were identified for urea at 27.50 (sensitivity: 100%, specificity: 73%, R2= 0.553, P